The migration of the family parents and its influence on the english language learning with the students at “Santiago Fernández García” high school, afternoon section of the “Calasanz” educational unit of the Loja city. Academic year 2009 – 2010 - Guillén Pineda, María de los Ángeles (2011)
The research work entitled: THE MIGRATION OF THE FAMILY PARENTS AND ITS INFLUENCE ON THE ENGLISH LANGUAGE LEARNING WITH THE STUDENTS AT “SANTIAGO FERNÁNDEZ GARCÍA” HIGH SCHOOL, AFTERNOON SECTION OF THE “CALASANZ” EDUCATIONAL UNIT OF THE LOJA CITY. ACADEMIC YEAR 2009 – 2010, has been made with the purpose of finding out the influence of the migration of the family parents on the learning of the English Language in the students at “Santiago Fernández García” afternoon section of the “Calasanz” Educational Unit of the Loja city. In the development of the research, we have made use of the scientific method as a general one which has helped to find the true about the researched object. And as particular methods we used the descriptive to describe the data, the analytic-synthetic to analyze the results and the explicative to explain the phenomena and to elaborate the report. In the field of work we applied the instrument of the survey to the teachers and the students, to process the information we have used a logical analysis with descriptive statistics that helped us to describe the results in tables and graphs. Among the main results of the research we found that most of the families that have traveled abroad have broken up their relationship as couple so that, the disintegration of families affects the migrants’ children academic outcomes. By the other hand those migrants’ children face emotional and behavioral problems at school which affect their academic and disciplinary outcomes in the English Language learning.